(untitled) (JOURNAL OF ADVANCES IN CHEMISTRY, 2012)
The distribution of Fe(II) between buffered aqueous solution and chloroform solution of N,N’-Ethylenebis(4-butanoyl-2-4-dihydro-5-methyl-2-phenyl-3H-pyrazol-3-oneimine)(H2BuEtP) was investigated. The effect of 4-butanoyl-2-4-dihydro-5-methyl-2-phenyl-3H-pyrazol-3-one(HBuP) in the distribution was also studied. Fe(II) concentration in aqueous raffinate was determined colorimetrically and distribution ratios and percentage extractions calculated by difference from Fe(II) in aqueous phase before and after equilibrations. The optimal pH for Fe(II) distribution slightly lowered to 8.00 in mixed ligands(H2BuEtP/HBuP) organic phase from 8.25 in ligand (H2BuEtP) alone organic phase. The pH range at which quantitative extraction of Fe(II) from aqueous buffered solution into both type of organic phases used for the study was very narrow. The extraction parameters; pH1/2, log D from extraction plots, and log Kex calculated using extraction equations derived from slope analysis showed that the values in both type of organic phases were very close even though mixed ligands(H2BuEtP/HBuP) organic phase values were slightly higher and better. Slope analysis also indicated that the Fe(II) complexes extracted into both organic phases were Fe(BuEtP)o and Fe(HBuEtP)(BuP)o respectively.